Apresentação - Fonseca, Vicente Fernandes Dutra (Revista da Extensão, 2019)
<span style="color: #111111; line-height: 115%; font-family: 'Myriad Pro','sans-serif'; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-fareast-language: PT-BR; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: PT-BR; mso-bidi-language: AR-SA;">Texto de apresentação da revista